The Influence of Service Quality and Brand Image on Customer Satisfaction and Customer Loyalty at the Pratama Marga Ayu Clinic in Badung, Bali - Atmajaya, I Putu Ogi; Negara, Gusti Ngurah Joko Adi; Santoso, Tri Priyono Budi; Junaedi, Wayan Ruspendi (The Eastasouth Management and Business, 2024)
This research investigates the impact of service quality and brand image on customer satisfaction and customer loyalty at the Pratama Marga Ayu Clinic in Badung, Bali. Using SPSS and Smart-PLS for analysis, the study reveals that both service quality and brand image significantly and positively affect customer satisfaction, which in turn influences customer loyalty. Additionally, customer satisfaction mediates the relationship between service quality and customer loyalty. The findings highlight the importance of enhancing service quality and brand image to foster higher customer satisfaction and loyalty. The research concludes with practical suggestions for improving service and brand image, including increasing healthcare personnel, enhancing branding efforts, and implementing customer loyalty programs. Future studies are recommended to explore other influencing factors such as product reviews, location, and social media marketing to further enrich the understanding of customer decision-making.